Simulação numérica do escoamento bifásico de líquido-gás no Interior de um rotor de uma bomba centrífuga radial - Prohmann, Pamella Roman (2017)
In the petroleum industry it is common the usage of electric submersible pumps as a technique of artificial lift to increase the production or to enable the production in non-natural flowing wells. However, the presence of gas in the pumped fluid may negatively influence the pump performance, which is directly related to the ability of the pump to increase pressure. In practice, the deterioration of this capacity causes a decrease on the petroleum production, which means economic loss. Nevertheless, the phenomena that cause performance degradation of centrifugal pumps under gas-liquid flows are poorly understood. The works from literature on this topic majorly rely on experimental methods. Studies with numerical methods are rarely found, while the ones that exists are simplified or not conclusive. In this context, the present work proposes a numerical study of the two-phase gas-liquid flow in a radial centrifugal pump rotor using the Computational Fluid Dynamics program ANSYS-CFX 17.2 (ANSYS, 2016). The rotor performance is evaluated as a function of several variables, such as the liquid and gas flow rates, the gas volume fraction and the gas bubble diameter. It was also investigated the dynamic of the liquid and the gas phases inside the rotor, in order to understand the phenomena that cause the decrease of the pump performance when operating with two-phase flows. Streamlines, velocity fields, gas phase distribution contours and the behavior of the velocity triangles are also examined for several operating conditions. This project contributes to the literature in this area as it adds knowledge about the two-phase flow in centrifugal pump rotors.